Penanaman Nilai-Nilai Islam Nusantara Di SMK PGRI Pandaan Pasuruan - Mukhammad Muzakki; Dewi Afiatul Qutsiyah (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine and analyze the instillation of Islamic Nusantara values ​​at SMK PGRI Pandaan Pasuruan as part of an effort to shape a generation that excels academically, professionally, and possesses religious character and Indonesian culture. This study used a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews with the principal, teachers, and students, and documentation of school activities. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the instillation of Islamic Nusantara values ​​at SMK PGRI Pandaan Pasuruan is implemented through targeted educational strategies, the instillation of religious attitudes, the integration of Islamic and national values ​​into the curriculum, and teacher role models in daily school life. Values ​​such as tolerance, peace, courtesy, mutual cooperation, and nationalism are implemented not only in teaching and learning activities but also in school culture, extracurricular activities, and social interactions. This process is capable of producing students who are not only competent in vocational skills but also possess integrity, spirituality, and a strong sense of national awareness. This study concludes that vocational education is not solely oriented towards the industrial world and practical skills, but can also coexist with values ​​education. Integrating the two produces graduates who are superior, professional, and religious, capable of contributing positively to maintaining social harmony and strengthening national identity. Thus, SMK PGRI Pandaan Pasuruan is an ideal model of values-based vocational education that prepares the younger generation to face global challenges without losing sight of their cultural, religious, and national roots. Abstrak Penelitian ini bertujuan untuk mengkaji dan menganalisis penanaman nilai-nilai Islam Nusantara di SMK PGRI Pandaan Pasuruan sebagai bagian dari upaya membentuk generasi yang unggul secara akademik, profesional dalam keterampilan, serta berkarakter religius dan berbudaya Nusantara. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, wawancara mendalam dengan kepala sekolah, guru, dan peserta didik, serta dokumentasi kegiatan sekolah. Analisis data dilakukan dengan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penanaman nilai-nilai Islam Nusantara di SMK PGRI Pandaan Pasuruan dilaksanakan melalui strategi pendidikan yang terarah, pembiasaan sikap religius, integrasi nilai keislaman dan kebangsaan dalam kurikulum, serta keteladanan guru dalam kehidupan sehari-hari di sekolah. Nilai-nilai seperti toleransi, cinta damai, sopan santun, gotong royong, dan nasionalisme diterapkan tidak hanya dalam kegiatan belajar mengajar, tetapi juga dalam budaya sekolah, kegiatan ekstrakurikuler, dan interaksi sosial. Proses ini mampu membentuk peserta didik yang tidak hanya kompeten dalam keterampilan kejuruan, tetapi juga memiliki integritas, spiritualitas, dan kesadaran kebangsaan yang kuat. Penelitian ini menyimpulkan bahwa pendidikan kejuruan tidak hanya berorientasi pada dunia industri dan keterampilan praktis, tetapi dapat berjalan beriringan dengan pendidikan nilai. Integrasi antara keduanya menghasilkan lulusan yang unggul, profesional, religius, serta mampu berkontribusi positif dalam menjaga harmoni sosial dan memperkuat identitas bangsa. Dengan demikian, SMK PGRI Pandaan Pasuruan menjadi model ideal pendidikan kejuruan berbasis nilai yang menyiapkan generasi muda siap menghadapi tantangan global tanpa kehilangan akar budaya, agama, dan kebangsaan.